Zad. 1
Przekształc wyrażenie na sumę i wykonaj redukcję wyrazów podobnych.
a 6(2a-6b+3c)
b (3x-2y+9)*4
d (4x-7y-7)(-2)
c 3(5x-8z-2)
e -8(7n+9p+t)
f -2(3a+1)+(4a-5)
g 3(b-5a)-2(3b+a)
h 5(2x+3y)-(x-2y)
i 4(x/4 + y/4)-5(3x/5 - 7y/5)
j -6(3x/6 - 2y/6)+2/3(3x/2-6y)

zad2
uprośc wyrażenie.
a 6(a+2b)-3(2a-3b)
b 4(b+3)+3(a-b)
c 7(b+c)-3(b+2c)
d 5(a+3)+2b-3(a+b)
e 6(3+z)-4(2z+4)+2(8+z)

1

Odpowiedzi

2010-03-02T15:15:13+01:00
Zad 1.
a 12a-+36b+18c
b 12x-8y+36
dalej z tego zad nie wiem ;/
sry ;/
zad2
6a+12b-3a-6b=3a+6b
4b+12+3a-3b=b+12+3a
7b+7c-3b-2c=4b+5c
5a+15+2b-3a-3b=2a+15-b
18+6z-8z-16+16+2z=18